Model Pengaturan Kedaruratan Dan Pilihan Kedaruratan Indonesia Dalam Menghadapi Pandemi Covid-19 - Arsil, Fitra; Ayuni, Qurrata (Jurnal Hukum & Pembangunan, 2023)
Indonesia own various of legal models uses to deal with emergencies. Two emergency arrangements in the 1945 Constitution are represented by the phrase "state of danger" in Article 12 of the 1945 Constitution and the phrase " coercive importance " in Article 22 of the 1945 Constitution. Both have different characters and implications for both the power generated and the oversight mechanism. In addition, there are also emergency legal instruments based on laws, which are represented among others by the Disaster Mitigation Act and the Health Quarantine Act. Interestingly, an emergency based on this law is not directly related to an emergency based on the Constitution which has implications for the legal system and character of the resulting emergency power. Dealing with the Covid-19 pandemic The Indonesian government was confronted with these choices to form an emergency policy. The choice of emergency legal scheme chosen by Indonesia is more for activating emergency based on the law in dealing with Covid 19.